ETIKA POLITIK ARISTOTELES: Kohesivitas Etika dan Politik - Hadi, Rahmad Tri; Arrasyid, Arrasyid (JURNAL AL-AQIDAH, 2021)
This article specifically describes and analyzes the cohesiveness between ethics and politics from Aristotle's thought. More specifically, he has written his thoughts in a book entitled Politics which has presented the concept of building the basic structure of the state and how to manage and distribute social justice (goodness). In human life, ethics and politics seem inseparable from human civilization. This is because this is one of the fundamentalist parts of the human paradigm and is difficult to separate. If politics is understood, as a “match”; "war"; "justify all means" will certainly give birth to politicians who are hungry for power (demoralization); who inherited animalistic traits. Instead, politics is interpreted by Aristotle in essence as "an effort to produce justice". The methods used are descriptive-analytical and historical methods with the aim of describing and analyzing the background and thoughts of Aristotle's political ethics as a whole. The results obtained first, the purpose of a country is to realize and maintain goodness. Here, it is as if Aristotle connects politics with goodness, namely ethics. Second, politics is the most important science and the most exalted thought which includes many good, and that all sciences serve it.